Evaluating the Science Experts Program at the Specialized Institute for Professional Training for Teachers in the Sultanate of Oman in Light of the Kirkpatrick Model (Journal Of Educational and Psychological Researches, 2023)
AbstractThis study aims to identify the degree to which the first cycle teachers use different feedback patterns in the E-learning system, to identify the differences in the degree of use according to specialization, teaching experience, and in-service training in the field of classroom assessment as well as the interaction between them. The study sample consisted of (350) female teachers of the first cycle in the governmental schools in Muscat Governorate for the academic year 2020/2021. The study used a questionnaire containing four different feedback patterns: reinforcement, informative, corrective, and interpretive feedback. The psychometric properties of the questionnaire were verified in terms of validity and reliability. Among the most prominent findings of the study: were that reinforcement feedback was the most frequently used feedback pattern from the teachers of the first cycle, and informative feedback was the least used. Also, there were statistically significant differences between the teachers in the degree of use of feedback patterns attributed to the variables of specialization and teaching experience, while there were no statistically significant differences between the teachers in the degree of use of feedback patterns due to the in-service training in the field of classroom assessment and the 2-way interactions between the variables. The study concluded with a set of recommendations and suggestions, including emphasizing the importance of female teachers employing different feedback patterns for students in the process of continuous assessment and conducting more studies on different feedback patterns and their effectiveness at various educational levels and subjects. The general level of the impact of the science experts program was very good from the graduates’ point of view. The results also revealed that there were no statistically significant differences between the means of graduates’ degree of satisfaction with the training program due to the variables of gender, training cohort, and years of experience. There were also no statistically significant differences between the means of the graduates’ ratings on the impact of the training program due to the variables of gender and training cohort. The study ended with a set of recommendations for developing the program and suggestions for future research studies. The most important recommendations are:Increase the number of field visits and continuing communication with graduates. The certificate obtained by graduates should have academic weight and the subjects taken in the training program should be equivalent to the master’s topics. Activating the professional learning communities in more effective ways to share experiences between teachers. Assign specific dates for teachers' training in the school calendar. Focus on improving the practical skills of teachers and not only theoretical parts.